Peripheral Orbital Schwannoma : A Case Report: Poster Presentation - Case Report - Ophthalmologist - TRI REJEKI HERDIANA; none (Majalah Oftalmologi Indonesia, 2023)
Introduction : The aim of this study was to report a rare case of a peripheral orbital nerve schwannoma. One of a thinkable diagnose and the goal of treatment. Case Illustration : A 17-years-old young lady with chief complaint was inferior eyelid lesion since 1 year and has gradually enlarged. Examination showed a space occupying lesion in the inferior right orbit around 10x5 mm that was firm to palpation, didn’t attach to the deep planes, painless, and did not displaced the eye. Computed tomography revealed a homogenous orbital mass, encapsulated, and did not invade adjacent structures Discussion : Lesion was treated with complete tumour resection via conjunctival / posterior site, and pathologic examination showed a schwannoma.Conclusion : Orbital schwannoma are infrequent tumours arising from the orbit coming behind inflammatory, vascular, and lymphoproliferative diseases. Treatment is complete resection of the lesion with subsequent monitoring to prevent recurrence.